Liberal Education Themes in the Philosophy of Methodological Anarchism of Paul K. Feyerabend - Agata Łopatkiewicz (Nicolaus Copernicus University in Toruń, 2014)
The paper aims at analyzing the conception of Austrian philosopher of science, Paul K. Feyerabend, for compatibility with the fundamental determinants of the conception of liberal education. The considerations are centered around attempts to answer the question of whether it is possible to indicate themes characteristic for Anglo-Saxon interpretation of the category of liberal education in the philosophy of methodological anarchism. The analysis begins with a brief presentation of the philosophical views of Feyerabend, including, in particular, the findings on the role and place of science amongst other ways to achieve knowledge, the idea of epistemological pluralism and the conditions for acceptability of cognitive perspective characteristic for humanities. Further investigations are focused on the conception of liberal education, with particular emphasis on its subjective and objective aspects. Characteristics of abovementioned topics give rise to the analysis of the title problem. The investigations are concluded with an affirmative answer to the question of relationship between methodological anarchism and the conception of liberal education, and indication of issues that require further study.